Treating acute cystitis with biodegradable micelle-encapsulated quercetin - Wang BL (Dove Medical Press, 2012)
Bi Lan Wang1, Xiang Gao1,2, Ke Men1, Jinfeng Qiu1, Bowen Yang3, Ma Ling Gou1, Mei Juan Huang1, Ning Huang2, Zhi Yong Qian1, Xia Zhao1, Yu Quan Wei11State Key Laboratory of Biotherapy and Cancer Center, West China Hospital, West China Medical School, 2Department of Pathophysiology, College of Preclinical and Forensic Medical Sciences, 3College of Life Science, Sichuan University, Chengdu, People’s Republic of ChinaAbstract: Intravesical application of an anti-inflammatory drug is an efficient strategy for acute cystitis therapy. Quercetin (QU) is a potent anti-inflammatory agent; however, its poor water solubility restricts its clinical application. In an attempt to improve water solubility of QU, biodegradable monomethoxy poly(ethylene glycol)-poly(ε-caprolactone) (MPEG-PCL) micelles were used to encapsulate QU by self-assembly methods, creating QU/MPEG-PCL micelles. These QU/MPEG-PCL micelles with DL of 7% had a mean particle size of ~34 nm, and could release QU for an extended period in vitro. The in vivo study indicated that intravesical application of MPEG-PCL micelles did not induce any toxicity to the bladder, and could efficiently deliver cargo to the bladder. Moreover, the therapeutic efficiency of intravesical administration of QU/MPEG-PCL micelles on acute cystitis was evaluated in vivo. Results indicated that QU/MPEG-PCL micelle treatment efficiently reduced the edema and inflammatory cell infiltration of the bladder in an Escherichia coli-induced acute cystitis model. These data suggested that MPEG-PCL micelle was a candidate intravesical drug carrier, and QU/MPEG-PCL micelles may have potential application in acute cystitis therapy.Keywords: nanomedicine, MPEG-PCL, self-assembly